Characterization of non-relativistic attosecond electron pulses by transition radiation from tilted surfaces. (5th March 2018) - Tsarev, M V; Baum, P
Abstract: We consider analytically and numerically the emission of coherent transition radiation by few-femtosecond and attosecond electron pulses. With optimized geometries based on tilted surfaces we avoid the influences of the beam diameter and velocity mismatch for sub-relativistic pulses. We predict the emission of visible and ultraviolet optical radiation that characterizes few-femtosecond or attosecond electron pulses in time. The total amount of radiation depends on the source' repetition rate and number of electrons per macro/microbunch and is in many cases sufficient for pulse length characterization in the emerging experiments.